The Influence of Environmental Cost and Environmental Performance towards Company’s Value Moderated by Ownership Structure - Duffin Duffin (UniSadhuGuna Business School, 2023)
This study aims to determine the influence of environmental cost and environmental performance towards company’s value. This study also examines the moderating effect of managerial ownership and institutional ownership on environmental cost and environmental performance towards company’s value. The object of this research is the participants of PROPER assessment that participates three years consecutively from year 2019-2021 that also listed in Indonesia Stock Exchange (IDX). The data analysis technique used in this study are the multiple linear regression and residual test. The results are: (1) environmental cost has negative and no significant influence towards company’s value, (2) environmental performance has positive and significant influence towards company’s value, (3) managerial ownership has moderating effect only on environmental cost relationship towards company’s value, and (4) institutional ownership has moderating effect only on environmental cost relationship towards company’s value. The theoretical implication is managerial and institutional ownership can strengthen environmental cost disclosure towards company’s value. The practical implications are the board of directors must consider optimum ownership structure to monitor and ensure that environmental cost disclosure is mandatory and make sure the operation of the companies is all according to the PROPER assessment standards. The government must establish a policy that obliges the publicly traded companies to disclose the environmental cost completely.